NILAI-NILAI BUDAYA DALAM NOVEL GENDUK KARYA SUNDARI MARDJUKI - Sitio, Desi Kristiani; Effendy, Chairil; Priyadi, Antonius Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the desire of researchers to find cultural values in the novel Genduk Karya Sundari Mardjuki. The problems discussed in this study are the nature of human life, the nature of human work, the nature of human beings in the space of time, the nature of human relations with nature, the nature of human relations with others, and the implementation of cultural values in Indonesian language learning at the high school / MA level. The purpose of this study was to describe the problem. The theory used in this study includes elements that build literary work, culture, elements of culture, cultural values, and literary learning.The method used is descriptive method with qualitative research forms. The approach used is literary anthropology. The data source is the Genduk Karya Sundari Mardjuki novel, while the data are in the form of quotations from the Genduk novels. Data collection techniques and tools in the form of documentary studies and researchers themselves. The technique of testing the validity of the data uses persistence of observation and triangulation.The results of the study of cultural values are (1) the nature of human life in the novel shows five forms of value, namely sincerity, accepting fate, keeping promises, patience, and nobility. (2) the nature of human work shows three forms of value, namely fulfilling needs, life, elevating degrees, satisfaction and pleasure. (3) the nature of human beings in the space of time shows a form of value that is the mindset of the past. (4) the nature of human relations with nature shows one form of value that human values depend on nature. (5) the nature of human relations with each other shows the form of values, namely responsibility, mutual cooperation, love, and help. (6) planned implementation of cultural values for learning Indonesian language and literature seen from aspects of curriculum, implementation plans, approaches, methods, media, and class X SMA / MA learning evaluations. Keywords: Value, Culture, and Novel